A Mathematical Analysis on the Dynamics of Macrophytes in Varthur lake, Bangalore (Journal of Pharmaceutical Negative Results, 2023)
In this paper, a case study is presented to study the effects of increasing nutrients and macrophytes on survival of fish population in Varthur lake, Bangalore, India. Several fish kill episodes have occurred in Varthur lake over past years. Aim of the present study is to investigate the effects mathematically as huge amount of nutrients from industries, domestic sewage is constantly release into the lake which is leading to abundant growth of macrophytes leaving less room for fish survival. The above-mentioned parameters are considered to formulate a mathematical model. Equilibrium points are studied and analysed in detail for stability via Routh-Hurwitz criteria. Numerical simulation is carried out to illustrate the analytical findings of the case study.